Autophagy protein 5 enhances the function of rat EPCs and promotes EPCs homing and thrombus recanalization via activating AKT. Issue 3 (September 2015) - Hu, Nan; Kong, Ling-shang; Chen, Hong; Li, Wen-dong; Qian, Ai-min; Wang, Xiao-yun; Du, Xiao-long; Li, Cheng-long; Yu, Xiao-bin; Li, Xiao-qiang
Abstract Deep venous thrombosis (DVT) is one of the most common peripheral vascular diseases. The roles of bone marrow-derived endothelial progenitor cells (EPCs) on the recanalization of venous thrombosis has been suggested recently, while the underlying mechanisms are not completely understood. Our objective was to investigate the functions of autophagy protein 5 (ATG5) in rat EPCs and its potential application in DVT. We have found that silencing of ATG5 or pharmacological suppression of ATG5 in rat EPCs reduces both the migration and psudotube formation under hypoxia in vitro. In line, overexpression of ATG5 significantly enhances the EPCs migration and psudotube formation capabilities. More importantly, injection of EPCs that stably express ATG5 increases EPC homing to the ischemic site and promotes thrombus recanalization in a rat DVT model in vivo. Mechanistically, we have shown that ATG5 overexpression enhances psudotube formation via the activation of AKT. These findings suggest that ATG5-AKT signaling plays an essential role in EPC migration and psudotube formation. Regulation of ATG5-AKT signaling may provide a potential novel therapy for DVT.